1980
DOI: 10.1116/1.570634
|View full text |Cite
|
Sign up to set email alerts
|

Submicron optical lithography using an inorganic resist/polymer bilevel scheme

Abstract: The Ag2Se/GeSe inorganic photoresist system has been used to produce submicron features by optical lithography. A practical process incorporating this material is the inorganic resist/polymer bilevel scheme. The successful printing of 0.5 μm lines and spaces is explained by the existence of an ’’edge sharpening’’ effect which accompanies the photo-doping process. Conventionally accepted limitations of photolithography are circumvented by the Ag2Se/GeSe resist, whose properties also include high contrast, resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
4

Year Published

1983
1983
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(19 citation statements)
references
References 0 publications
0
15
0
4
Order By: Relevance
“…The resin was first annealed 15 min at 85°C, then insolated through a metallic mask thanks to a mercury vapor lamp (S.E.T MG 1400), 250 W. The insolated bands of 15 lm in width were dissolved by dipping the resin in a MF319 commercial remover. Physical [9,10] and reactive physical [11][12][13] etchings were performed on the films. An ALCATEL-DION 300 RF-sputtering set-up was used for physical etching in an argon atmosphere (5 Pa Ar).…”
Section: Methodsmentioning
confidence: 99%
“…The resin was first annealed 15 min at 85°C, then insolated through a metallic mask thanks to a mercury vapor lamp (S.E.T MG 1400), 250 W. The insolated bands of 15 lm in width were dissolved by dipping the resin in a MF319 commercial remover. Physical [9,10] and reactive physical [11][12][13] etchings were performed on the films. An ALCATEL-DION 300 RF-sputtering set-up was used for physical etching in an argon atmosphere (5 Pa Ar).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, often an all-dry process is desired from the manufacturing point of view (Kovalskiy et al, 2006). Generally, cF 4 and SF 6 + o 2 plasmas are used for chG or chG-ag binary system patterning, which behave as negative resist (Kostyukevych, 1998;Tai et al, 1980). notwithstanding, a way to obtain positive resist with Rie is proposed, where the as 33 S 67 -ag structure is dry etched in S plasma (Kozicki et al, 1991).…”
Section: Dry Etchingmentioning
confidence: 99%
“…Edge sharpening is a negative factor for the formation of high-fidelity lithographic patterns, especially grayscale and 3D structures. interestingly, edge sharpening has been suggested also as a way to obtain nanometer size features by photodiffusion, much finer than the wavelength employed for diffusion, due to the compensation of diffraction and interference effects (Tai et al, 1980). We have also shown that the edge sharpening effect depends on the method of preparation (Kovalskiy et al, 2006).…”
mentioning
confidence: 95%
“…A consequence of photo-doping is a drastic decrease in the solubility of the chalcogenide. Therefore the phenomenon was used to develop application such as holography [3], photography [4] and photoresist of submicronic resolution [5]. The electrical, optical, photoelectrical and physicochemical properties of photo-doped samples, as well as the dissolution of silver under the action of agents other than light were reported in detail in the review by Kolobov and Elliott [6].…”
Section: Introductionmentioning
confidence: 99%